Taboo and Health Behavior of Mahout in Elephant Biosphere of Thailand and Lao Peopleâ€™s Democratic Republic - Boonmee, Somsri; Chanawongse, Krasae; Uttisaen, Malinee; Rewdang, Kittima (Mediterranean Journal of Social Sciences, 2012)
The In-Depth Interview was done with 5 leaders of mahouts (Elephant Charmers). The content from qualitativeresearch was analyzed to construct the 97 items for quantitative research. Factor analysis was used for determination thecomponent factors of health behavior of the Elephant Charmers, mahouts and their families in Thailand. The survey research,questionnaires were used for data collection from 530 Elephant Charmers, mahouts and their families in Surin Province ofThailand. Data was analyzed exploratory factors analysis and group discussion. The objectives of this research were to studyhealth autobiography, taboo and health behavior of Elephant Charmers, mahouts and their families in elephant biosphere ofThailand and Lao Peopleâ€™s Democratic Republic, and to analyze component factor of heath behavior; propose ways to improvehealth behaviors of mahouts and their families in Thailand. The results of the research were as the followings. The healthautobiography and health behavior of 5 Elephant Charmers (leaders of mahouts), key informants in both Thailand and Laos,aged 81-89 years, known as â€œMhor sa-diangâ€, â€œMhor Sa-dumâ€ and â€œKru-ba-yai or Ti-yaiâ€ were found in 5 aspects of health;Physical with well-being, Emotional with good temper, Social with the leadership, Spiritual self-reliance and Intellectual with goodmemory. They were the leaders of community rites. They could raise warm and strong families by being careful, proudly,practicing in the taboo and the principle of Buddhism without exploitation. They lived consistently with the Sufficiency EconomicPhilosophy. The taboo of mahouts in elephant biosphere of Thailand and Lao Peopleâ€™s Democratic Republic were the same asin daily activities; such as, eating, sitting, walking, sleeping, worshipping â€œPa Kamâ€ spirits and practicing the dharma. They wereeven more strict in their daily lives during the wild elephant round-up. The factors analysis, the five components related to heathbehavior of Elephant Charmers, mahouts, and their families in Thailand included 1) The procedure and food for health, 2) Thefamily relationship, 3) The strict practice in morals and the principle of Buddhism, 4) The credibility leadership, and 5) Thegenerosity and non-exploit.